Perbedaan Umur Tanaman Penghijauan Terhadap Perubahan Kualitas Tanah di Desa Pelaga, Kecamatan Petang, Badung - MARBUN, JUWITA ROHAYATI; SUSILA, KETUT DHARMA; SUNARTA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.3, Juli 2018, 2018)
Differences of Greening Planting Ages Against Soil Quality Changes in Pelaga Village, Petang District, Badung Land as an environmental component must be maintained, protected and avoided from adverse impacts and must be maintained and enhanced. This study aims to determine the effect of different age of reforestation plants on soil quality changes in Pelaga Village, Petang District, Badung Regency. The method used in this research is observation method with direct observation in field and laboratory analysis. The research was conducted in accordance with several stages, namely the planning and preparation of the initial survey of reforestation land that aims to determine the point of sampling in accordance with the age of reforestation, soil sampling, analysis of physical properties, chemistry, and biology in the laboratory and analysis of research data. The results showed that there was no change in soil quality on land with different plantation age 1 year, 2 years, 3 years, compared with control (land with grass vegetation) and decreased soil quality was observed on land with planting age 4 years and 5 years (after harvest).